On a new species of the genus Cyprinotus (Crustacea, Ostracoda) from a temporary wetland in New Caledonia (Pacific Ocean), with a reappraisal of the genus - Martens, Koen; Yavuzatmaca, Mehmet; Higuti, Janet (European Journal of Taxonomy, 2019)
The New Caledonia archipelago is known for its high level of endemism in both faunal and floral groups. Thus far, only 12 species of non-marine ostracods have been reported. After three expeditions to the main island of the archipelago (Grande Terre), about four times as many species were found, about half of which are probably new. Here, we describe a new species, Cyprinotus drubea sp. nov., which is characterised mainly by the hyper-developed dorsal hump on the right valve, much larger than in any other known Recent species in this genus. After a literature study of the other presumed species in Cyprinotus Brady, 1886, we retain seven Recent species in the genus, including the present new species. Cyprinotus crenatus (Turner, 1893), C. dentatus (Sharpe, 1910), C. flavescens Brady, 1898, C. inconstans Furtos, 1936, C. newmexicoensis Ferguson, 1967, C. ohanopecoshensis Ferguson, 1966, C. pellucidus (Sharpe, 1897), C. scytodus (Dobbin, 1941) and C. sulphurous Blake, 1931 are here all referred to the genus Heterocypris s. lat. Claus, 1892. Cyprinotus unispinifera Furtos, 1936 is assigned to the genus Cypricercus Sars, 1895. Cyprinotus tenuis Henry, 1923, C. fuscus Henry, 1919 and C. carinatus (King, 1855) are here classified as doubtful species. A checklist of the 14 non-marine ostracods, now including Cyprinotus drubea sp. nov. and Cypris granulata (Daday, 1910), thus far reported from New Caledonia, is provided. Herpetocypris caledonica Méhes, 1939 and H. caledonica var. minor Méhes, 1939 are synonymised with Candonocypris novaezelandiae (Baird, 1843).